Analisis Simbol Sisingaan Sebagai Kesenian Subang - Prawiyogi, Anggy Giri; Ramdani, Masdi Salimudin; Rosalina, Annita; Suparman, Tarpan; Dewi, Sinta Maria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Sisingaan is an art originating from Sunda Land, which is more precisely in Subang Regency, West Java. This art emerged from the time of the Dutch colonialists in Indonesia, where the initial purpose of this art was to show the manifestation of resistance to the invaders, which at that time the people of Subang were colonized by the Dutch colonialists. However, as time goes by, the art of Subang develops and preserves into the art ofSubang which is usually displayed at circumcision events in the Subang area. The method used in this research is descriptive qualitative with ethnopedagogic approach. Where ethnopedagogy is an approach in education that is based on culture (local wisdom) and emphasizes the importance of human relations which aims toexamine the pedagogical dimension through a sociological perspective of pedagogy. Data collection techniques are: 1) literature review by reviewing relevant literature such as articles in journals, youtube and books and various research results on Sisingaan; 2) On December 1, 2021, conduct direct interviews with sources with Kang Anggis as a comparison and increase knowledge about Sisingaan which is a typical art originating from Subang, followed by observations and documentation of artistic observations to the actors of Sisingaan art. The results of the study can be concluded that Sisingaan art is an art that emerged and developed in the Tanah Sunda area, namely in Subang Regency. Which was originally as a manifestation of resistance to Dutch colonialism. But over time this art developed into an art that is usually found in circumcision activities. Hopefully in the future Sisingan art will remain sustainable and become a cultural heritage in Subang Regency.